piv does not impact Pseudomonas aeruginosa virulence in Galleria mellonella - Rachel E. Robinson; Joshua K. Robertson; Dina A. Moustafa; Joanna B. Goldberg (Microbiology Spectrum, 2025)
ABSTRACT Pseudomonas aeruginosa is an opportunistic human pathogen that can also infect mammals, invertebrates, and plants. Protease IV (PIV) is a secreted protease shown to be important in mammalian cornea, lung, and wound models of infection. It also contributes to P. aeruginosa virulence in many invertebrate models. Previous studies have shown that the expression of the gene encoding PIV is higher at 25°C than at 37°C. Thus, we hypothesized that piv would be more important for P. aeruginosa virulence at 25°C than at 37°C. To test this, we first demonstrated that more PIV is secreted by P. aeruginosa PAO1 cells grown at 25°C than at 37°C. We then determined the survival of larvae of the greater wax moth Galleria mellonella infected by PAO1 and an isogenic Δpiv mutant at both 25°C and 37°C. We found no significant difference in virulence between PAO1 and Δpiv at either 25°C or 37°C, although both strains were more virulent at 37°C than 25°C as measured by a decrease in median survival time. P. aeruginosa possesses an arsenal of virulence factors besides PIV, and thus loss of this single virulence factor may not result in attenuation in the highly susceptible G. mellonella larvae.IMPORTANCEPathogenesis of the important opportunistic pathogen Pseudomonas aeruginosa is often investigated using model organisms. Larvae of the greater wax moth, Galleria mellonella, are a popular non-mammalian model organism for P. aeruginosa infections that have been used to study highly attenuated mutants and characterize their defects in virulence. Our study shows that small differences in the virulence of P. aeruginosa, such as those caused by deleting the gene encoding a single virulence factor, may not be detectable in the G. mellonella model of infection. This is an important finding for researchers considering the choice of model organisms for virulence studies.